Psychiatrization of adoption practices in contemporary Poland - Witeska-Młynarczyk, Anna (Frontiers in Sociology, 2022)
In this article, I propose to take a closer look at the practices of kinning in the context of adoption in contemporary Poland. I am interested in the social production of this ‘unfamiliar kind of kinship' and the positions of various actors involved in defining the “adoptable” children and the “families of excess” capable of adopting. My focus will be on the ways in which the psy-knowledge and practices are implied in these social processes of defining and delimiting the norm, the proper, and the ideal. This process can be called a progressing psychiatrization of kinning, this time developing on a specific terrain of adoption (i.e., the most desired state of exception from ideal family—nuclear, heteronormative, based around married, and non-divorced couple). I will consider both top-down and bottom-up processes within which the individuals, state institutions, and psy-knowledge interact. Thus, I propose to look at a sub-process of psychiatrization, which takes place in the specific ethnographic context at the intersection of family and social policies, medicalization and psychologization of familial relations, and troubled, disconnected biographies. Throughout the article, I discuss how the adoptive families become patient-consumers within the system of healthcare. It is despite the fact that when they enter the adoption network, they start to take part in the political process of solving the social problem. In fact, they become a part of the network, which enables privatization of the social problem and works toward individualizing the responsibility for solving it.